The Politeness of Teachers’ Imperative Speech Acts in Teacher–Student Interactions in Senior High School: A Sociopragmatic Approach - Muhammad Chaidir; Syamsuddin Syamsuddin; Ulinsa Ulinsa (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to describe, analyze, and interpret the forms, functions, and politeness strategies of teachers’ imperative speech acts in teacher–student interactions at Senior High School 1 Poso Pesisir Utara using a sociopragmatic approach. Methodology: This study employed a qualitative descriptive method using observation, audio recording, and note-taking techniques. Data were analyzed through Miles and Huberman’s interactive analysis model, involving data reduction, data display, and conclusion drawing. The analysis applied Sudaryanto’s formal and informal presentation methods without any statistical or software-based tools. Main Findings: The study identified 17 forms of polite imperative speech acts, including directive, requestive, persuasive, and advisory types. Teachers applied Leech’s six politeness maxims tact, generosity, approbation, modesty, agreement, and sympathy to balance authority and respect. Two politeness strategies, direct and indirect, were used depending on context, social distance, and communicative goals. Teachers consistently maintained ethical, polite, and culturally sensitive communication. Novelty/Originality of this study: This study provides a detailed sociopragmatic analysis of teachers’ imperative speech acts within an Indonesian multicultural school context. It highlights how local linguistic features and cultural norms influence the realization of politeness in educational communication, offering new insights into the intersection of language, culture, and pedagogy rarely explored in previous research.